Administrative data provide vital research evidence for maximizing health‐system performance and outcomes. Issue 3 (24th January 2017) - Roder, David; Buckley, Elizabeth
Abstract: Although the quality of administrative data is frequently questioned, these data are vital for health‐services evaluation and complement data from trials, other research studies and registries for research. Trials generally provide the strongest evidence of outcomes in research settings but results may not apply in many service environments. High‐quality observational research has a complementary role where trials are not applicable and for assessing whether trial results apply to groups excluded from trials. Administrative data have a broader system‐wide reach, enabling system‐wide health‐services research and monitoring of performance markers. Where administrative data raise questions about service outcomes, follow‐up enquiry may be required to investigate validity and service implications. Greater use should be made of administrative data for system‐wide monitoring and for research on service effectiveness and equity.